REVIEW OF TAILBINDU PARIKSHA AND ITS PRACTICAL APPLICABILITY IN AYURVEDA - Sarnaik Swati Pandit; Shaha Reshma R (International Journal of Applied Ayurved Research, 2016)
Indian traditional medicine,Ayurveda has a great history. Diagnosis according to Ayurveda is not merely naming the disease but identification of imbalance of trienergies doshas. Tailbindu pariksha, an ancient method of urine examination for ascertaining the prognosis of disease, the use of which became obsolete after 17th century AD. Prognosis is an important aspect of disease & treatment; It can help to assessing the disease. From ancient time predicting, prognosis has always been a big challenge to the medical profession. If we look into Ayurvedic texts then we will find that art of prognosis was well developed in ancient times. A tail bindu pariksha, knowing prognosis was popular. In tail bindu pariksha, urine taken in glass vessel over which an oil dropped & behavior of oil is noted, the features are indicative of as a diagnostic & prognosis of disease. This is popular prognostic & diagnostic tool in past but now a days this is not specifically used, so there is need to review their results so that they can be used in future. In present article, mutra pariksha has been reviewed in various aspect of disease & the technique as predicting diagnosis & prognosis approach are described. On the basis of mutra pariksha, assessing prognosis & severity of disease to plan the treatment & helpful in healthy condition also. Since no laboratory test is available to instantly assess or forecast the prognosis of disease, this method is very cost effective may be proved to be useful technique in this field.